Peningkatan Ekonomi Masyarakat Melalui Penanaman Hidroponik Oleh Kelompok Wanita Tani (KWT) di Kelurahan Pegambiran Kecamatan Lemahwungkuk Kota Cirebon - Istiqomah Istiqomah (ICODEV: Indonesian Community Development Journal, 2022)
Economic growth also affects food demand, in line with population growth and an increase in the economic value of the community. In the development of agricultural products, there is now another way to utilize the narrow land for the purpose of developing agricultural products, namely the hydroponic method. The Women Farmers Group (KWT) is a forum that can be a hope for farmer families, because the resources they have can be used as a special forum for women farmers in an effort to empower families. In this study, researchers used a qualitative narrative method of research results, in an effort to improve the community's economy through the hydroponic planting program by the Women Farmers Group (KWT) is to increase family income from the wife through hydroponic planting activities whose results can be resold, not only in terms of but also KWT members can develop their potential and take advantage of available natural resources. The purpose of this study was to determine the improvement of the community's economy through hydroponic planting by the Women Farmers Group (KWT) in Pegambiran Village, Lemahwungkuk District, Cirebon City.